A Framework for Scaffolding Learners’ Self-Regulation in a Flipped Classroom Learning Environment - Farhana Jumaat, Nurul; Che Lah , Noor Hidayah (KnE Social Sciences, 2022)
Self-regulated learning is learning that is derived from a student’s self-regulated thoughts and it is strategically oriented towards their learning goals. The need to guide and monitor students’ self-regulation is crucial since it has become an integral part of their learning process. Throughout the process, technologies also have been integrated into the educational scene, and one of the approaches that exist nowadays is flipped classrooms. Previous research has proven that if a student’s self-regulation is being monitored, their performance might as well increase, along with their selfregulation skills. As a result, this paper proposes a framework for scaffolding students’ self-regulation in a flipped classroom learning environment. The proposed framework may be useful to practitioners and online learning instructors. The implication of a self-regulated flipped classroom approach towards students’ self-regulation and students’ achievement in learning have been discussed. Finally, the success factors for implementing the proposed framework and some future research directions have also been discussed. Keywords: scaffolding; self-regulated; flipped classroom; performance